A luz é para todos, mas a cidadania é para poucos? avaliando os possíveis impactos do Programa Luz Para Todos (PLPT) no processo de inclusão social da população beneficiária no Maranhão (2003 a 2022) - BEZERRA JÚNIOR, José Tavares (2023)
This thesis had as a research plan to carry out an impact assessment of the Light for All (PLPT) implemented in Maranhão. The Program was created in 2003 with the aim of universalizing access to electricity throughout Brazil and, in addition, to embody a policy to combat poverty. Through the critical-dialectical method, a historical rescue and investigation of the phenomenon of rural electrification was carried out. The empirical space was limited to six villages, belonging to three municipalities in Maranhão, based on the correlation between low HDI and the number of families benefiting from the arrival of energy. Data and information were collected through semi-structured interviews and focus groups with former residents who witnessed the arrival of energy, community leaders, rural workers, city hall managers, trade unionists, among others, making a total of 103 direct participants. It was observed that the PLPT is a successful program, despite having generated both positive and negative impacts, the latter being linked, for the most part, to management problems at the local energy distributor and, moreover, as a result of the inefficiency on the part of the government, within the specificity of the six villages visited. Among the impacts, effects and positive results, we have the productive use of energy, food conservation, development of activities that generate employment and income, access to goods and services, use of energy in schools, health centers and community wells of water catchment. In terms of negative impacts, effects and results, there is an increase in the beneficiaries' indebtedness, non-compliance with quality indicators in the energy supply (DEC/DEF), electrical damage to home appliances, problems related to public lighting, various non-conformities found audited by the Comptroller General of the Union (CGU), among others. After the initial investment phase, the operation and maintenance phases of the electricity network did not progress satisfactorily, in addition to universalization not serving all families and many, therefore, still remain without energy or with access via clandestine connection. It was concluded that articulation with other programs is essential for the PLPT to effectively become a facilitating axis of social inclusion, especially for the rural proletariat.